Analysis of students’ creative thinking on plant microtechnical laboratory practices: Analysis of students’ creative thinking skills on Plant Microtechnique laboratory practices - E. Ermayanti; Yenny Anwar; Didi Jaya Santri (University of Muhammadiyah Malang, 2021)
Empowerment of creative thinking skills is important in every lecture activity, including practicum. This study aimed to analyze students' creative thinking skills in Plant Microtechnique practicum. This research used descriptive method in which the participants were the seventh semester biology education students (n=20) of State University of South Sumatera, Indonesia. The student has taken Plant Microtechnique Course in the previous semester. The instrument used was essay test developed based on creative thinking indicator. The data were processed by calculating the percentage for each indicator and categorized into three levels (i.e., low, medium, and high). The findings revealed that students’ creative thinking skills in Plant Microtechnique laboratory practices were medium for fluency indicator, and low for flexibility, originality, and elaboration indicators. Therefore, it is necessary to revise learning strategies that support the empowerment of students' creative thinking in Microtechnique Laboratory practices.